Innovative Application Software for Tourism Safety in World Heritage Site Si Satchanalai Historical Park - Louhapensang, Chaturong; Kangkhao, Surasak (My University, 2018)
Implementations of safety measures ranked among major concerns for all involving parties in tourism industry-from both the public and private sectors and civil society-since they these procedures could generate either positive or negative effects on livelihood in a community, economic progress, social practice, and physicality of the built environment. Today, as information technology (IT) had increasingly been integrated with travel activities, this paper presented an exploratory research on an application software for tourism safety, experimented at the UNESCO World Heritage Site in Si Satchanalai Historical Park in Thailand. In effect, the aims of the Smart World Heritage Si Satchanalai Application (SWHSA) were to supply tourists with a customizable, diversified, and cost-effective cybernetic means to conceive and organize their travel planning, which could be tailored to suit particular needs of the users according to their: 1) travel durations; 2) types of leisure activities; and 3) numbers of attractions preferred to see in a certain length of time. As shown by the upcoming analytical and evaluative discussions, the said criteria were specified by the distance, in conjunction with variety and distribution of places intended to visit per day by the users. Altogether, the investigations on SWHSA demonstrated its values in terms of an interactive IT model that provided multifaceted information-which not only: 1) helped the inhabitants and state authority in Si Satchanalai monitor and respond to evolving situations on tourism safety in real time; and 2) enabled travelers to expediently plan their trips as they desired.
Keywords: Application Software; Experimental Study; Heritage Management; Mobile Application; Si Satchanalai Historical Park; Tourism Safety at UNESCO World Heritage Site